Design : Automatic Irrigation Tools on Chili Plants Using Microcontractor-Based Soil Moisture Sensor - Suparman Suparman; Arief Ika Uktoro; Muhammad Rendi (Tropical Plantation Journal, 2026)
The cultivation of chili plants (Capsicum annuum L.) still faces problems in irrigation management that are not yet data-based, causing less efficient water use and risking reducing the productivity of chili harvests. This research aims to design an automatic watering system using soil moisture sensors and microcontrollers integrated with web dashboards and Google Sheets for real-time monitoring and control of soil moisture. The method used is engineering research which includes designing hardware and software, calibrating soil moisture measuring instruments and implementing tools in chili fields. The result of this research is to produce a soil moisture measuring tool in the form of a prototype that can be used for automatic irrigation of chili plants. The calibration results obtained an accuracy level of 99.73% and a tolerance of 0.27%, and the tool is able to water automatically when the soil moisture is dry, namely at soil moisture less than 60% RH. The tool can automatically save data to Google Sheets. This tool system is declared suitable for use as a precision irrigation solution in chili cultivation.